A Quantitative study of kite performance in natural wind with application to kite anemometry - Hobbs, Stephen (Cranfield University, 1986)
Although kites have been around for hundreds of years and put to many uses, there has so far been no systematic study of their performance. This research attempts to fill this need, and considers particularly the performance of kite anemometers. An instrumented kite tether was designed and built to study kite performance. It measures line tension, inclination and azimuth at the ground, :sampling each variable at 5 or 10 Hz. The results are transmitted as a digital code and stored by microcomputer. Accurate anemometers are used simultaneously to measure the wind local to the kite, and the results are stored parallel with the tether data. As a necessary background to the experiments and analysis, existing kite information is collated, and simple models of the kite system are presented, along with a more detailed study of the kiteline and its influence on the kite system. A representative selection of single line kites has been flown from the tether in a variety of wind conditions. The results from these experiments are analysed to obtain general performance measurements for these kites in real, turbulent, winds. The analysis is taken a stage further to evaluate the kites for anemometry, and to study the dynamics of the kite system. The most suitable kites for anemometry are identified, together with the wind conditions in which they may be used and the wind information available from measurements at the tether. The study ends with a review, and a discussion of useful areas of further work. [This digital (pdf ) version of the thesis was created in August 2005. The content is identical to that of the original paper copy of 1986, although the layout and pagination differs in detail. Readers should note that anemometer calibrations described in Hobbs (1994) suggest that the windspeed values given in this thesis are incorrect by a few percent: however, the general conclusions about kite performance stated in the thesis are unaffected by these changes.]